До питання про процедурні норми як елемент правового регулювання забезпечення державними соціальними допомогами - Вознюк, Н.; Vozniuk, N. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті досліджуються питання встановлення змісту процедурних правових норм у сфері державних соціальних допомог, визначено їх місце у реалізації правових приписів. Сформульовані особливі видові характеристики процедурних норм права у сфері державних соціальних допомог. The article highlights the issues of procedural norms content definition in the field of state social security and explores the importance of these norms for realization of legal prescriptions. It has been revealed that the content of procedural norms in the sphere of state social assistance/benefits implies the regulation of the positive (in contrast to the negative - controversial) activity of the subjects of legal relations aimed at the realization of the right to state social security within the material procedure. The importance is placed on the structural components of the social security benefits. As a result of the analysis of the procedural norms content in the field of state social assistance their specific features have been revealed: they regulate the positive activity of subjects of legal relations as to the implementation of the right to state social benefits within the framework of material procedure; regulate organizational and legal activities of the authorized entities; they are not collected in a separate regulatory legal act but are combined with the material norms; they fix procedural deadlines and are ensured not by coercive measures, but by negative consequences that may occur in case of non-compliance with the procedure; they are the regulatory rules of law; the main form of their implementation is their fulfillment, which implies performance of active and timely practical work.
The Procedural Norms as an Element of Legal Regulation for Providing State Social Security Benefits
Keywords: соціальне забезпечення; державна соціальна допомога; правове регулювання державних соціальних допомог; процедурні норми у сфері державних соціальних допомог; ознаки процедурних норм у сфері державних соціальних допомог; social security; state social security benefits; legal regulation of state social benefits; procedural norms in the sphere of state social security benefits; features of procedural norms in the sphere of state social benefits